Application of Oxidative Ring Opening/Ring Closing by Reductive Amination Protocol for the Stereocontrolled Synthesis of Functionalized Azaheterocycles - Kiss, Loránd; Ouchakour, Lamiaa; Nonn, Melinda; Remete, Attila M. (Synlett, 2021)
The current Account gives an insight into the synthesis of some N-heterocyclic β-amino acid derivatives and various functionalized saturated azaheterocycles accessed from substituted cycloalkenes via ring C=C bond oxidative cleavage followed by ring closing across double reductive amination. The ring-cleavage protocol has been accomplished according to two common approaches: a) Os-catalyzed dihydroxylation/NaIO4 vicinal diol oxidation and b) ozonolysis. A comparative study on these methodologies has been investigated. Due to the everincreasing relevance of organofluorine chemistry in drug research as well as of the high biological potential of β-amino acid derivatives several illustrative examples to the access of various fluorine-containing piperidine or azepane β-amino acid derivatives are also presented in the current Account.1 Introduction2 Olefin-Bond Transformation by Oxidative Ring Cleavage3 Synthesis of Saturated Azaheterocycles via Oxidative Ring-Opening/Ring-Closing Double Reductive Amination3.1 Importance of Fluorine-Containing Azaheterocycles in Pharmaceutical Research3.2 Synthesis of Azaheterocyclic Amino Acid Derivatives with a Piperidine or Azepane Framework through Oxidative Ring Opening/Reductive Amination3.2.1 Synthesis of Piperidine β-Amino Esters3.2.2 Synthesis of Azepane β-Amino Esters3.2.3 Synthesis of Fluorine-Containing Piperidine γ-Amino Esters3.3 Synthesis of Tetrahydroisoquinoline Derivatives through Oxidative Ring Opening/Reductive Amination Protocol3.4 Synthesis of Functionalized Benzazepines through Reductive Amination3.4.1 Synthesis of Benzo[c]azepines3.4.2 Synthesis of Benzo[d]azepines3.5 Synthesis of Various N-Heterocycles via Ozonolysis/Reductive Amination3.5.1 Synthesis of Compounds with an Azepane Ring3.5.2 Synthesis of Piperidine β-Amino Acids and Piperidine-Fused β-Lactams3.5.3 Synthesis of γ-Lactams with a Piperidine Ring3.5.4 Synthesis of other N-Heterocycles4 Summary and Outlook5 List of Abbreviations
Keywords: azaheterocycles; ring opening; ring expansion; reductive amination; fluorine